Assessment of Pericardial Fat Volume by Cardiac CT and Its Relation With Coronary Heart Diseases - Soliman Belal Soliman; Azza Samy Ali Mohamad Etman; Ragab Hani Mohamad Donkol; Ahmed Mohamad Abo Elyazed Ramadan (Egyptian Journal of Critical Care Medicine)
Abstract Background Coronary artery disease (CAD) is the leading cause of morbidity and mortality. Pericardial fat includes both epicardial (located within the pericardium) and paracardial fat (located superficial to the pericardium). Pericardial fat may play a central role in the pathogenesis of cardiovascular disease, mediated by its inflammatory properties. Objective The objective of this study was detection of the predictive and/or diagnostic value of pericardial fat volume for patients with CAD using coronary CT angiography and its relation with coronary artery calcium score and other comorbidities of CAD. Patients and Methods Fifty-eight patients with a clinical suspicion of CAD were referred to CT unit in Radiology Department asking for CT coronary angiography for the possibility of CAD between December 2020 and June 2021. All patients were well prepared and underwent CT according to the standard protocol. Coronary artery calcium was quantified, and pericardial fat volume (PFV) was measured. Coronary arteries were systematically analyzed to evaluate anatomic distribution, detection and localization of coronary artery lesions, and qualitative and quantitative assessment of obstruction of the vessel caused by the lesion. Results There is a statistically significant correlation between PFV and CAD (P < 0.001). We considered PFV ≥120 cm3 as the cutoff value for development of CAD, with an area under the ROC curve of 0.65, achieving 80.6 % sensitivity and 63.4 % specificity. Our study showed that PFV has high statistically significant correlation with calcium score (P < 0.001). In addition, our study revealed significant relation between pericardial fat volume and hypertension, diabetes, and dyslipidemia (P = 0.006, 0.01, and 0.01, respectively). Conclusion Pericardial fat volume has good prognostic value for developing coronary artery diseases, and increased PFV is considered a risk factor of CAD and correlated with other risk factors of CAD, such as age, hypertension, hyperlipidemia, diabetes, and calcium score.